Effects of 16 Weeks of Muay Thai Training on the Body Composition of Overweight/Obese Adolescents - Saraiva, Bruna Thamyres Ciccotti [UNESP]; Scarabottolo, Catarina Covolo [UNESP]; Christofaro, Diego Giulliano Destro [UNESP]; Silva, Gabriela Caroline Rodrigues [UNESP]; Junior, Ismael Forte Freitas [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Ritti-Dias, Raphael Mendes; Milanez, Vinicius Flavio (My University, 2021)
Background. To analyze the effects of 16 weeks of Muay Thai training on the body composition of overweight/obese adolescents. Problem and Aim. The objective of study is to analyze the effects of 16 weeks of Muay Thai training on the body composition (fat mass, lean mass, and bone mass) of overweight/obese adolescents. Methods. Thirty-three overweight / obese adolescents, aged between 10 and 17 participated in the study, being allocated to the training (n=18) and control (n=15) groups. Anthropometric measurements and body composition were measured using dual energy X-ray absorptiometry, in which the variables of body mass, body fat, fat mass, lean mass, density, and bone mineral content, were collected by total and by segment. Results. After 16 weeks of training with MT, the effect on a significant group, with changes in body mass was observed (ΔMT = 0.79; ΔControl = -0.21), body fat percentage (ΔMT = -2.89; ΔControl = -0.67), total fat mass (ΔMT = -1.78; ΔControl = -0.6), fat mass of the arms (ΔMT = -0.38; ΔControl = -0.01), trunk fat (ΔMT = -2.74; ΔControl = -0.16) and android fat (ΔMT = -2.8; ΔControl = -0.62). The mean total lean mass (MM) (ΔMT = 2.81; ΔControl = 0.27) and the MM of the legs (ΔMT = 1.2; ΔControl = 0.1). Conclusions. Training with MT caused significant increases MM in total and in the legs.
Keywords: adolescents; martial arts; obesity; overweight; training